Effect of plant growth regulators and deficit irrigation on canopy traits, yield, water productivity and fruit quality of eggplant (Solanum melongena L.) grown in the water scarce environment. (15th May 2020) - Wakchaure, G.C.; Minhas, P.S.; Meena, Kamlesh K.; Kumar, Satish; Rane, Jagadish
Abstract: Deficit irrigation (DI) and plant growth regulators (PGRs) have strategic role for sustaining crop productivity and mitigating water stress in drought prone areas. However, their impacts are yet to be quantified for eggplant ( Solanum melongena L.), a popular drought tolerant vegetable crop grown in water scarce Deccan Plateau of India. We conducted field experiments during 2016–17 and 2017–18 in a drought prone region of Deccan Plateau, India to evaluate the interactive effect of PGRs viz., 1.38 mg L −1 salicylic acid (SA), 1.5% potassium nitrate (PN), 500 ppm thio-urea (TU) and 100 ml L −1 bio-stimulant (BS) and varied levels of DI generated using line source sprinkler system. The marketable fruit yields were reduced to 86, 74, 50, 30, 12 and 8% with increased level of DI i.e. when the applied irrigation water (IW) equalled 0.00, 0.15, 0.30, 0.45, 0.60 and 0.75 times the cumulative open pan evaporation (CPE) against the recommended irrigation practice (IW:CPE 0.90). Application of PGRs improved fruit yields by 7.3–22.7% and their role to alleviate water stress was indicated by lower canopy temperatures, maintaining higher leaf relative water content, modulation of stomatal opening and higher consumptive use of water. Particularly SA and TU were superior under low to medium water stress (IW:CPE 0.45–0.75) whereas PN was effective in severe water stress (IW:CPE 0.0–0.44) while the effect of BS was almost similar with PGRs like TU under medium stress conditions. The maximum water productivity (WP) varied between 5.50 and 6.77 kg m −3 for different PGRs and it was 5.16 kg m −3 without PGRs indicating water savings to the order of 28.8–57.4% with the former. The fruit quality attributes such as mean diameter, sphericity, fruit weight and firmness traits declined with water stress while these were considerably rectified with PGRs. Higher accumulation of dry matter, sugar, protein, total phenolics, flavonoids and improved rehydration quality as well as potentially affecting enzymatic activity were monitored with PGRs. It is concluded that exogenous application of PGRs like SA and PN along with medium levels of DI can help in rational utilization of water resources and could effectively improve yield and post-harvest quality of eggplant fruits especially under water scarce environment of Deccan Plateau. Graphical abstract: Image 10186 Highlights: Eggplant responses to PGRs and DI practices in water scarce environment were investigated. PGRs improved fruit yield (7.3–22.7%) and water productivity (5.50–6.77 kg m −3 ). Salicylic acid (SA) and potassium nitrate (PN) were found effective in alleviating water stress. PGRs with medium DI upregulated marketable and physicochemical fruit quality characteristics.